Repurposing of PSMA-targeted diagnostic and therapeutic agents for the detection and treatment of giant cell tumors of bone - McAllister, Brenna C.; Mesbahi, Nooshin; Dodson, Esther E.; Abdulsalam, Sakinah; Berkman, Clifford E.; Caromile, Leslie A. (Frontiers in Oncology, 2024)
Giant cell tumor of bone (GCTB) is a rare bone tumor often necessitating surgical intervention, radiation therapy, or treatment with bisphosphonates or denosumab. 99mTc-MDP bone scintigraphy for GCTB has limited specificity, and the relatively high uptake of 18F-FDG in GCTB makes it challenging to differentiate it from other benign bone tumors. More specific detection and treatment modalities for GCTB are needed to enhance patient monitoring and outcomes. Prostate Specific Membrane Antigen (PSMA) is present in the neovasculature of various tumors, yet unexplored in GCTB. PSMA-targeted imaging and radiotherapeutic agents Locametz and Pluvicto are a powerful theranostic pair for detecting and treating PSMA-positive metastatic tumors, including those in bone, and thus have considerable potential to be repurposed for GCTB. This study aimed to determine if the vasculature of GCTB was PSMA-positive and whether targeting it with PSMA-specific agents was feasible. Using bone core samples from 28 GCTB patients and 9 negative controls, we present the first robust detection of PSMA on the tumor vasculature of GCTB. To demonstrate the potential repurposed use of PSMA-targeted agents in detecting and treating GCTB, we used a PSMA-specific fluorescent probe (FAM-C6-1298) as a model for these radiopharmaceutical agents. Incubation of fresh GCTB tissue samples with FAM-C6-1298 showed increased fluorescence intensity compared to controls, indicating successful targeting of PSMA in GCTB tissue. In conclusion, our data established that PSMA is not only present in the tumor vasculature of GCTB patient tissue but can be effectively targeted with repurposed PSMA-specific radiopharmaceuticals for diagnosis and therapy.